2016
DOI: 10.5812/ircmj.25008
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Patterns in the Elderly Kashan Population

Abstract: BackgroundPhysical activity is an important component of health in old age that provides personal independence, physical ability, and quality of life.ObjectivesThe current study aimed to evaluate physical activity and associated factors among the elderly population in Kashan, Iran.Patients and MethodsThis is a descriptive cross-sectional study. The sample was 400 elderly people (aged more than 60 years) living in Kashan, Iran in 2014. The subjects randomly selected via multi-stage cluster sampling from healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
4
13
3
Order By: Relevance
“…16 In terms of gender differences, a body of research shows that women are less likely to participate in PA than men. For example, in a quantitative study about older adults, also comprised of data from self-administered questionnaires, women were found to be less physically active than men, due to personal and environmental restrictions related to PA. 24 The authors' results are also in line with an Iranian quantitative study that reported a significant relationship between PA, marital status, and gender, but in contrast with our study, that study found significant relationships between PA, age, educational level, and health status, 25 perhaps due to the difference between demographic characteristics of the two samples. Another cause of this inconsistency may be related to the fact that this study included a sample of physically active older adults who were found in parks.…”
Section: Discussionsupporting
confidence: 90%
“…16 In terms of gender differences, a body of research shows that women are less likely to participate in PA than men. For example, in a quantitative study about older adults, also comprised of data from self-administered questionnaires, women were found to be less physically active than men, due to personal and environmental restrictions related to PA. 24 The authors' results are also in line with an Iranian quantitative study that reported a significant relationship between PA, marital status, and gender, but in contrast with our study, that study found significant relationships between PA, age, educational level, and health status, 25 perhaps due to the difference between demographic characteristics of the two samples. Another cause of this inconsistency may be related to the fact that this study included a sample of physically active older adults who were found in parks.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study showed that active elderly women had higher physical health than sedentary elderly women. The results of this study were consistent with Sadrollahi et al, Giuli et al and Ghasemzadeh et al (2013), which showed that decreased BMI could promote all subscales of quality of life [3,26,27] , but not consistent with the findings of Fabrie et al and Trif et al [28,29] . One of the issues that could contribute substantially to improving the quality of life of the elderly is regular and continuous physical activity.…”
Section: Discussionsupporting
confidence: 82%
“…The results of our research showed active elderly women had higher social relationships than elderly women with compatatively lower physical activity. The results of this study were consistent with the studies of Ghasemzadeh et al and Kouzechian et al [26,35] but were not consistent with the study of Azin et al [36] . Aging has unique physical, mental and social characteristics.…”
Section: Acknowledgementsupporting
confidence: 60%
“…According to the world health organization (2009), more than 60% of the world population do not have physical activities of moderate intensity (6). Surveys conducted in Iran also showed that 80 percent of the Iranian people are physically inactive (7). According to some studies (e.g.…”
Section: Introductionmentioning
confidence: 99%